Mechanistic investigation of quercetin in the management of diabetic foot ulcer by network pharmacology and molecular docking - Riya Singla; Sonia Kamboj; Jasmine Chaudhary; Randhir Singh (Pharmacological Research - Modern Chinese Medicine, 2024)
Background: Quercetin (QUE), being a strong antioxidant, has been a part of Chinese traditional medicine for ages for the management of a large number of ailments including type 2 diabetes mellitus and its complications, primarily, Diabetic Foot Ulcer (DFU), but it is under lying mechanisms remain elusive. The introduction of network pharmacology and molecular docking has made it facile to investigate the mechanism of QUE-containing different plants and to validate the binding affinity of QUE with DFU protein respectively. Aim: This study is aimed to investigate the mechanism of QUE in protecting against DFU through modern approaches viz. network pharmacology and molecular docking. Materials and methods: The traditional Chinese medicine system pharmacology analysis platform (TCMSP) has been used to retrieve the active ingredients in various Chinese formulations. QUE was found to be a bioactive component of various Chinese formulations. The core therapeutic targets of QUE against DFU were identified using a protein–protein interaction (PPI) network. QUE-associated targets and genes related to DFU were obtained from different comprehensive databases (Pubchem, Swiss target prediction database, SEA database, String database, DisGeNET database, Molegro virtual docker version 6.0, ADMET lab2.0, SwissADME database) were intersected, and analyzed to obtain mapping targets and ranked to obtain key targets. Results: The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway shows major pathways were obtained from for QUE was matrix metallopeptidase 9 (MMP9). Receptor-ligand interaction between QUE with MMP9 were evaluated via MVD 6.0 software. A total of 10 interactions of quercetin with the following moldock score, rerank score, and H-bond interactions were observed as -110.912, -37.33, and -12.11 respectively. Candidate targets MMP9 in diabetic complications were ascertained and found associated with QUE against the management of DFU. Molecular docking models showed that QUE could closely bind to the key targets MMP9 (PDB id: 2OVX). ADME/T Analysis is performed to check the pharmacokinetic and toxicity profile which complies with the ideal values. Conclusions: This study proposed MMP9, as the key target of bioactive QUE in mechanistic control of DFU by lowering the activity of the IL-17 signalling pathway, Leukocyte trans-endothelial migration, Fluid shear stress, and atherosclerosis respectively. Future aspects: The explication of mode of action of bioactive constituent QUE against DFU provide a theoretical basis for designing more promising agents further for treatment of DFU in diabetic patients.